2008
DOI: 10.1016/j.bmc.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of human antibodies neutralizing Bacillus anthracis toxin

Abstract: A less than adequate therapeutic plan for the treatment of anthrax in the 2001 bioterrorism attacks has highlighted the importance of developing alternative or complementary therapeutic approaches for biothreat agents. In these regards passive immunization possesses several important advantages over active vaccination and the use of antibiotics, as it can provide immediate protection against Bacillus anthracis. Herein, we report the selection and characterization of several human monoclonal neutralizing antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…It is possible, therefore, that the greater affinity of 2-B12 for its target, compared to the affinities of 14B7 and 1-F1, compensates for the fact that 2-B12 binds to a region of PA outside the receptor recognition domain. Several groups have recently documented the importance of antibody affinity in the neutralization of anthrax toxins (1,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible, therefore, that the greater affinity of 2-B12 for its target, compared to the affinities of 14B7 and 1-F1, compensates for the fact that 2-B12 binds to a region of PA outside the receptor recognition domain. Several groups have recently documented the importance of antibody affinity in the neutralization of anthrax toxins (1,46).…”
Section: Discussionmentioning
confidence: 99%
“…This MAb contacts the face of domain 4 that is involved in receptor recognition, and has been proposed to encompass residues 671 to 721. Certainly, additional neutralizing epitopes exist on domain 4 (1,46). In particular, Abboud and Casadevall (1) suggested a linear epitope, immediately adjacent to or possibly overlapping the 14B7 binding site, as the target of neutralizing antibodies.…”
mentioning
confidence: 99%
“…Moreover, several studies also indicate that antibodies to both EF and LF can protect experimental animals from challenge with anthrax toxins or bacteria (1,7,9,19,32,38,39). Therefore, investigations in our laboratory are focused on defining protective responses to LF and EF components of the tripartite anthrax toxin and using this information to design new vaccination approaches that include well-defined determinants of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another advantage of therapeutic mAbs is the predictability of their pharmacodynamic (PD) and -kinetic (PK) properties, a critical aspect in drug development (Reichert, 2003;Reichert and Valge-Archer, 2007). In light of the potent 3-oxo-C 12 -HSL-mediated cytotoxicity, it might be appropriate to think of it as a bacterial toxin and mAbs have successfully been used as neutralizing agents for a variety of bacterial toxins (Casadevall et al, 2004;Nowakowski et al, 2002;Zhou et al, 2007). Here, we have demonstrated that the quorum quenching antibody RS2-1G9 can efficiently protect murine macrophage from the detrimental effects of the P. aeruginosa quorum sensing molecule 3-oxo-C 12 -HSL.…”
Section: Discussionmentioning
confidence: 99%